2021
DOI: 10.1002/ece3.7541
|View full text |Cite
|
Sign up to set email alerts
|

Diel patterns of predation and fledging at nests of four species of grassland songbirds

Abstract: Although it is common for nestlings to exhibit a strong bias for fledging in the morning, the mechanisms underlying this behavior are not well understood. Avoiding predation risk has been proposed as a likely mechanism by a number of researchers. We used video surveillance records from studies of grassland birds nesting in North Dakota, Minnesota, and Wisconsin to determine the diel pattern of nest predation and fledging patterns of four ground‐nesting obligate grassland passerines (Grasshopper Sparrow ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…In particular, the mortality of dependent young appears to be a ubiquitous and important factor shaping life history traits across avian species (summarized in Martin & Briskie 2009) and is therefore predicted to play a critical role in shaping fledging times across songbird species (Chiavacci et al 2015). However, there is still a paucity of studies on variation in diel patterns and duration (how rapidly nestlings in a brood leave the nest) of fledging across songbird species (Ribic et al 2021); as such, we lack even basic information about fledging for most species (Johnson et al 2013). This gap in our knowledge is largely a result of technological and logistical limitations of observing fledging behaviour at larger scales and across species (Johnson et al 2004(Johnson et al , 2013; however, technological advancements have allowed recent studies on the timing and duration of fledging in songbirds (Chiavacci et al 2015, Radersma et al 2015, Ribic et al 2018, Santema et al 2021.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, the mortality of dependent young appears to be a ubiquitous and important factor shaping life history traits across avian species (summarized in Martin & Briskie 2009) and is therefore predicted to play a critical role in shaping fledging times across songbird species (Chiavacci et al 2015). However, there is still a paucity of studies on variation in diel patterns and duration (how rapidly nestlings in a brood leave the nest) of fledging across songbird species (Ribic et al 2021); as such, we lack even basic information about fledging for most species (Johnson et al 2013). This gap in our knowledge is largely a result of technological and logistical limitations of observing fledging behaviour at larger scales and across species (Johnson et al 2004(Johnson et al , 2013; however, technological advancements have allowed recent studies on the timing and duration of fledging in songbirds (Chiavacci et al 2015, Radersma et al 2015, Ribic et al 2018, Santema et al 2021.…”
mentioning
confidence: 99%
“…Despite the limited literature on the fledging of birds, a common finding from past studies is the tendency of songbirds to fledge in the morning (usually within 6 h after sunrise or before midday (astronomical noon)) and for all brood mates to fledge rapidly, usually within a couple hours of the first nestling to leave (Lemel 1989, Johnson et al 2004, Schlicht et al 2012, Chiavacci et al 2015, Ribic et al 2018, Santema et al 2021. Additionally, the 'survival hypothesis' predicts that the predation of dependent offspring in the nest drives songbirds to fledge earlier in the day (Chiavacci et al 2015, Ribic et al 2021. Although evidence for the hypothesis is mixed, past research has shown links between overall rates of nest predation and variation in fledging times across species (Chiavacci et al 2015).…”
mentioning
confidence: 99%
See 3 more Smart Citations